Sclerosing Bone Dysplasia from 16th Century Sardinia (Italy): A Possible Case of Camurati–Engelmann Disease. (September 2016) - Giuffra, V.; Montella, A.; Bianucci, R.; Milanese, M.; Tognotti, E.; Caramella, D.; Fornaciari, G.; Bandiera, P.
Abstract: The skeletal remains of a male aged 45–55 years displaying several bone anomalies were unearthed from the Alghero (Sardinia) plague cemetery 'lo Quarter', a burial site dating back to the 1582–1583 AD outbreak. The skeleton, whose stature is about 165 cm, presents a bilateral hyperostosis with increased diameter of the diaphyses of all the long bones of the upper and lower limbs; the metaphyses appear to be involved, while the epiphyses are spared. Marked thickening of the cranial vault is also evident. Radiological study showed irregular cortical thickening and massive endoperiosteal bone apposition; sclerotic changes are observed in the diaphysis of some metacarpals. Computed tomography (CT) cross sections of the long bones displayed a thickening of the cortical portion and endoperiosteal bone apposition. The individual was affected by a sclerosing bone dysplasia, a genetic disease characterized by increased bone density. In differential diagnosis, several sclerosing bone dysplasia, such as hyperostosis corticalis generalisata, craniodiaphyseal dysplasia, craniometadiaphyseal dysplasia, pachydermoperiostosis and Camurati–Engelmann disease, as well as other disorders characterized by sclerosing manifestations, such as Erdheim–Chester disease, mehloreostosis and skeletal fluorosis, need to be considered. The anomalies observed in skeleton 2179 fit with the features of Camurati–Engelmann disease, which is the most likely candidate for final diagnosis. It is highly challenging to evaluate how such a condition may have influenced the individual's lifestyle in terms of development, mobility and quality of life. This individual was probably symptomatic and must have experienced common clinical symptoms, such as pain in the limbs and fatigability. However, the strong development of the muscular insertions and the degenerative changes in the upper limbs suggest that the mobility problems should not have prevented him from reaching a mature age and from performing essential daily activities. The presented case is the unique paleopathological evidence of Camurati–Engelmann disease so far diagnosed. Copyright © 2015 John Wiley & Sons, Ltd.